Kebersyukuran dan pemaknaan ulang sebagai prediktor terhadap koherensi diri pada mahasiswa organisator - Chrysan Gomargana; Yonathan Aditya (Jurnal Psikologi Ulayat, 2022)
This study aimed to provide evidence regarding how gratitude and positive reframing serve as predictors on student activists’ levels of sense of coherence in a private university in Tangerang. Data was collected from a sample of 140 students who were active members of student organizations. The Gratitude Questionnaire Six-Item-Form (GQ-6) was used to measure gratitude, Positive Reframing Measurement (PRM) was used to measure positive reframing, and Sense of Coherence Scale 13 Items (SOC-13) was used to measure sense of coherence. The result exhibited a significant contribution of gratitude and positive reframing toward student activist’s level of sense of coherence and all its dimensions. Other findings related to these variables, limitations of the study, and future research directions are also discussed.